Embryonic and larval development of the striped mullet Mugil cephalus (L) - Abraham, Mathew; Shiranee, P; Chandra, P Kishore; Kailasam, M; Charles, V K (Indian Journal of Fisheries, 2011)
Mugil cephalus in ripe condition collected from inshore catches at Muttukadu near Madras were induced to breed using HCG and ovaprim to study the embryonic and larval development. Samples of unfertilised eggs and various developmental stages from fertilization through embryonic and larval stages were preserved for further micrographic studies. Rate of fertilization was determined at the time of blastodisc formation and was 90 %. Of the total number of 1.46 million eggs, 1.26 million were fertilised. The pre-hatched embryo was deeply pigmented, exhibited twitching movements and lay curved over the yolk mass. After an incubation period of 30-32 hrs, the embryo hatched out. The newly hatched out larvae measuring 2.29 mm, were transparent with a large oval head, a well defined yolk sac and short tail encircled by a continuous finfold. Mouth formation was complete and the larvae started feeding on 3rd day of hatching. The paper presents the results of detailed studies of embryonic and larval development and the time scale established for critical stages of development.